SEXUALITY EDUCATION THROUGH AUDIO-VISUAL MEDIA: IMPACTS ON PRESCHOOLERS’ KNOWLEDGE AND SKILLS - Zahro, Ria Fatimatuz; Safitri, Rani; Ilmiah, Widia Shofa (CV. TOTUS TUUS, 2025)
Child sexual violence remains an urgent problem in Indonesia, exacerbated by cultural taboos and limited access to effective sex education for young children. This study aimed to evaluate the effectiveness of sexuality education using audio-visual media in improving knowledge and self-protection skills among preschoolers aged 4–5 years at TK Muslimat NU 5 Irama, Malang. Employing a quantitative, pre-experimental one-group pretest–posttest design, the research involved 48 students selected through simple random sampling. Data collection utilized structured interviews and observation checklists, analyzed using descriptive statistics and the Wilcoxon signed-rank test. The results revealed a significant improvement: the proportion of children with poor knowledge and skills declined sharply, while those in “good” and “very good” categories increased substantially after the intervention (p < 0.05). These findings demonstrate that audio-visual media can effectively convey essential concepts about body safety and appropriate touch, overcoming barriers associated with traditional or text-based methods. The study concludes that integrating interactive, age-appropriate media into early childhood education enhances both cognitive and practical domains of sexuality education. The research supports broader implementation of innovative, media-based strategies in preschool and midwifery settings to promote child protection and abuse prevention. Future studies are recommended to explore longitudinal effects, parental involvement, and scalability across diverse educational contexts.